ASSOCIATION OF HAEMATOLOGICAL PARAMETERS WITH CARDIOVASCULAR RISK FACTORS IN POPULATION OF DISTRICT SHAHEED BENAZIRABAD SINDH, PAKISTAN (The Research of Medical Science Review, 2025)
BACKGROUBD: Every year, cardiovascular diseases (CVDs) cause more fatalities than any other ailment, making them the primary cause of morbidity and mortality globally. The Purpose of this study was analysis the correlation between hematological parameters and CVD risk factors. METHODOLOGY: This research, which was carried out in District Shaheed Benazirabad, Sindh, Pakistan, between 2019 and 2020, was planned as a descriptive cross-sectional study. A total sample size of 312 was enrolled Aged≥ 20 years and (43) individuals were excluded from the present study due to having different clinical disorders remaining finally (269) normal healthy adults were selected using a random sampling method. Blood samples were analyzed for fasting blood glucose (FBG), lipid profile, and complete blood count (CBC), with statistical analysis performed using SPSS. RESULTS: Present study shows that increased blood pressure and cholesterol levels are linked to higher hemoglobin and hematocrit levels in males, which may raise the risk of CVD. Higher RBC, Hb, and platelet counts, however, are associated with higher blood pressure and lipid abnormalities in females, suggesting a connection between dyslipidemia and hypertension. All things considered, these results point to the importance of hematological indicators in determining cardiovascular risk, especially when it comes to blood pressure and lipid metabolism. CONCLUSION: The study highlights strong associations between hematological markers and CVD risk factors, with gender-specific differences. These findings suggest that incorporating hematological markers in routine risk assessments could aid in early detection and prevention of CVD.